2015
DOI: 10.1111/aos.12745
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of bevacizumab, ranibizumab and aflibercept on cell viability, phagocytosis and mitochondrial bioenergetics of retinal pigment epithelial cell

Abstract: ABSTRACT.Purpose: To evaluate the short-and long-term effects of most clinically used anti-vascular endothelial growth factor agents, including bevacizumab, ranibizumab or aflibercept, on cell viability, phagocytosis, mitochondrial bioenergetics and the oxidant acrolein-induced oxidative stress of human adult retinal pigment epithelial (ARPE)-19 cells. Methods: In cultured ARPE-19 cells, cell viability was measured by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay, phagocytotic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
1
20
0
1
Order By: Relevance
“…There was no apparent difference on RPE viability for different concentrations of glucose in the presence of hypoxia. Anti‐VEGF drugs have been shown to have a non‐significant effect on RPE and ARPE‐19 viability, and these investigations were not repeated in this study . Glucose appears to have a beneficial effect on the RPE in vitro.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There was no apparent difference on RPE viability for different concentrations of glucose in the presence of hypoxia. Anti‐VEGF drugs have been shown to have a non‐significant effect on RPE and ARPE‐19 viability, and these investigations were not repeated in this study . Glucose appears to have a beneficial effect on the RPE in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…Anti-VEGF drugs have been shown to have a nonsignificant effect on RPE and ARPE-19 viability, and these investigations were not repeated in this study. [20][21][22][23][24] Glucose appears to have a beneficial effect on the RPE in vitro. High glucose has been associated with increased proliferation of ARPE-19 as well as affecting the morphology of these cells.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, in a previous study by Malik et al, [24] neither Ranibizumab or Aflibercept produced any evidence of mitochondrial beneficial effect at clinical doses, whereas mitochondrial toxicity was observed at clinically relevant doses. In contrast, Sheu et al, [32] hypothesized that the early protective action on mitochondrial bioenergetic capacity could predict possible long-term antioxidative effects of Aflibercept and Ranibizumab in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…18 In this study, bevacizumab treatment, but not aflibercept or ranibizumab treatment, suppressed the phagocytic activity of human ARPE-19 cells. Based on the results of cell viability and phagocytic activity assays, it was suggested that the mechanism of action of bevacizumab differs from that of aflibercept and ranibizumab in ARPE-19 cells.…”
Section: Figmentioning
confidence: 56%
“…ranibizumab (0.125, 0.25, or 0.5 mg/mL), or aflibercept (0.125, 0.5, or 2.0 mg/mL). 18 We used 0, 0.25, 0.5, 1.0, and 2.0 mg/mL concentrations, which include the clinical dose for the vitreous. However, we tested HCECs which are different from the previous cells tested ( .…”
Section: Figmentioning
confidence: 99%